Congenital Insensitivity to Pain with Anhidrosis (CIPA): The First Reported Case in Bangladesh (Journal of Current and Advance Medical Research, 2023)
Congenital insensitivity to pain with anhidrosis (CIPA) is also known as hereditary sensory and autonomic neuropathy type IV. It is an exceedingly rare autosomal recessive disease which occurs due to lack of maturation of small myelinated and unmyelinated fibers of peripheral nerves. These fibers are required for transmission of pain and temperature sensation. This disorder is characterized by insensitivity to pain with intact tactile perception, anhidrosis, self mutilation, recurrent unexplained fever, auto amputation, mental retardation & autonomic nervous system abnormality from infancy. The clinical presentation of a 4-year-old boy with this rare disease is worth to describe, as the first case to be reported in Bangladesh. Rehabilitative treatments for prevention of disease complications and their progress should be given emphasis in every encounterJournal of Current and Advance Medical Research, July 2022;9(2):91-94